2019
DOI: 10.1007/s12192-019-01007-w
|View full text |Cite
|
Sign up to set email alerts
|

Role of AccMGST1 in oxidative stress resistance in Apis cerana cerana

Abstract: As detoxification enzymes, proteins in the glutathione S-transferase (GST) superfamily are reported to participate in oxidative stress resistance. Nevertheless, microsomal GSTs (MGSTs), a unique subclass of the GST superfamily associated with membranes, are rarely studied in insects. Here, we isolated an MGST gene in Apis cerana cerana (AccMGST1) and verified its role in oxidative stress response. We found higher expression of AccMGST1 in protective or defensive tissue, that is, the epidermis, which indicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…In many animals, changes in the antioxidant and metabolic systems after exposure to temperature stress have been demonstrated. In this study, honeybees were exposed to low and high temperatures, which differentially induced the expression of AcZFP41 in their bodies (Figure 4a,b), suggesting that cold and high temperature induce intracellular oxidative stress through different pathways (Zhao et al, 2019). In addition, UV light, which is the most harmful and mutagenic part of the solar spectrum, causes oxidative stress and induces damage to proteins and plasma membranes (Cadet et al, 2005; Ravanat et al, 2001).…”
Section: Discussionmentioning
confidence: 66%
“…In many animals, changes in the antioxidant and metabolic systems after exposure to temperature stress have been demonstrated. In this study, honeybees were exposed to low and high temperatures, which differentially induced the expression of AcZFP41 in their bodies (Figure 4a,b), suggesting that cold and high temperature induce intracellular oxidative stress through different pathways (Zhao et al, 2019). In addition, UV light, which is the most harmful and mutagenic part of the solar spectrum, causes oxidative stress and induces damage to proteins and plasma membranes (Cadet et al, 2005; Ravanat et al, 2001).…”
Section: Discussionmentioning
confidence: 66%
“…Furthermore, to analyze the effects of AccMGST2 silencing on ROS levels in A. cerana cerana , we examined the expression of antioxidant genes, including AccSOD2 (Jia et al, 2014), AccGSTS4 (Yu et al, 2012), AccTpx3 (Yao et al, 2013), AccP450 (Zhu et al, 2016), AccGSTD (Yan et al, 2013), AccTrxr1 (Yang et al, 2010) and AccMGST1 (Zhao et al, 2019), in A. cerana cerana after AccMGST2 silencing. The results showed that the expression levels of most genes were downregulated to varying degrees, suggesting that AccMGST2 silencing may affect the antioxidant system in A. cerana cerana .…”
Section: Discussionmentioning
confidence: 99%